2005
DOI: 10.1038/nn1618
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular taxonomy of major neuronal classes in the adult mouse forebrain

Abstract: Identifying the neuronal cell types that comprise the mammalian forebrain is a central unsolved problem in neuroscience. Global gene expression profiles offer a potentially unbiased way to assess functional relationships between neurons. Here, we carried out microarray analysis of 12 populations of neurons in the adult mouse forebrain. Five of these populations were chosen from cingulate cortex and included several subtypes of GABAergic interneurons and pyramidal neurons. The remaining seven were derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
518
2
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(549 citation statements)
references
References 48 publications
26
518
2
2
Order By: Relevance
“…A similar approach has been also successfully utilized for the analysis of distinct subtypes of brain neurons (Fischer et al 2004;Yao et. al., 2005;Sugino et al 2006) and astrocytes (Cahoy et. al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach has been also successfully utilized for the analysis of distinct subtypes of brain neurons (Fischer et al 2004;Yao et. al., 2005;Sugino et al 2006) and astrocytes (Cahoy et. al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We performed an overrepresentation analysis using the Gene Ontology (GO) database to perform a functional characterization of the deregulated proteins and established a GO map as described in ref. 12. This revealed that one-third of the proteins have functions in mitochondria, specifically complex I and IV (Table 1).…”
mentioning
confidence: 97%
“…Like BK channels, activation of Kv3 channels can shorten AP duration. Intriguingly, a study that examined the gene expression profile of populations of CNS neurons revealed an inverse relationship between the levels of GluR2 mRNA and that of Kv3.1 with many GABAergic interneurons expressing high levels of Kv3 and low levels of GluR2 (Sugino et al 2006). In this study, we show that blockade of BK channels can increase the expression of GluR2-containing receptors in GABAergic interneurons in the cerebellum.…”
Section: Discussionmentioning
confidence: 47%
“…Several types of GABAergic interneurons are known to express high levels of potassium channels, including Kv3 and large-conductance Ca 2ϩ -activated potassium (BK) channels (Bartos et al 2007;Perney et al 1992;Rudy and McBain 2001;Sugino et al 2006). These channels display a characteristic high activation threshold and generate noninactivating currents, which accelerate the repolarization of APs.…”
mentioning
confidence: 99%